An Assessment on the Denominational Tendencies of Akkoyunlus - Sohrabiabad, Hamidreza (Journal of Alevism-Bektashism Studies, 2018)
The Bayındır clan that arose around the mid of the 14th century as a strong political and social organisation, succeeded to be one of the most important states in middleage Turkish history by gathering other clans comprised generally of Turkmens. The Akkoyunlu State, formed thus, prepared the ground for Turkish states, established after it in the same region, with the political tradition which Akkoyunlus had shaped for almost one hundred and fifty years of existence.In this context, comprehending the state mentioned and its tradition, asserted on the level of a state tradition, will enable the linear interpretation of the history of Turkish states. Accordingly, the reasons for the development of states established in the same region after Akkoyunlus, their internal dynamics, the principles of etatism and the mental world of Turkmen man will become transparent.Belief world occurs as one of the guiding basic elements in the picture drawn in our study. Because, religious perceptions and denominational tendencies constitute one of the main elements in the Akkoyunlu culture, as in every country and social layer.So far, the researchers have generally qualified Akkoyunlus as Sunni, and on top of that they have described their rulers as real, strict, even fanatical Sunni. Although the researchers in question have adduced findings which support their theses, most of the facts and findings are based on political relations between Akkoyunlus and other states, and the conclusions unavoidably diverged from the essence. The mentioned researchers, on the other hand, have generally focused on the official religion of the state and rulers.This study attempts to digress from depictions made to date. It analyses the part of detecting a state’s religious character through political connections, in reaching the reliable results. Besides, it explores religious tendencies among population, especially in the eyes of Turkmens, in the period of the Akkoyunlus’ rulership, particularly starting from the example of the Diyarbakir Province.The analysis attempts to show through historical data and official documents, recently revealed, as against existing perspective, that the Akkoyunlu rulers were inclined toward folk Islam/ pre-Qizilbash-Alevism and that the Turkmens, who constituted the state’s backbone, were seriously attached to the mentioned belief system. Therefore, it is possible to think of the Safavid Empire as a continuation of Turkish state tradition in the context of religious characteristics.
Keywords: Akkoyunlu; pre-Qizilbash; Alevi; Qizilbash; Safavid